Anxiety Disorders in Major Depressive Disorder Patients in a Tertiary Care Hospital in Bangladesh (Community Based Medical Journal, 2026)
Anxiety disorders frequently co-occur with major depressive disorder (MDD), potentially complicating clinical presentation and treatment outcomes. Anxiety disorders can exacerbate symptoms and impact the overall quality of life, necessitating comprehensive diagnostic and therapeutic approaches. A cross-sectional study was conducted at the Department of Psychiatry, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and June of 2021, to evaluate the prevalence, features, and severity of anxiety disorders in patients with major depressive disorder. A total of 77 patients with major depressive disorder attending the outpatient department (OPD) of the hospital were enrolled in this study through convenient purposive sampling technique. The severity of anxiety was assessed using the Hamilton Anxiety Rating Scale (HAM-A). Demographic and clinical data was recorded and analyzed. The HAM-A scale indicated that 29.9% of participants had mild anxiety (score ≤17), while 44.2% had mild to moderate anxiety levels (score 18-24). Those who experienced moderate to severe anxiety (score 25-30) comprised 20.8% and 5.2% experienced severe anxiety (score >30). In 46.8% of participants, the anxiety types were identified. Approximately 24.7% were diagnosed with generalized anxiety disorder, while obsessive-compulsive disorder was found in 7.8%, and panic disorder in 5.2% of the cases. Almost half of individuals with major depressive disorder (MDD) may also experience mild to moderate anxiety disorders. Generalized anxiety disorder is the most prevalent, potentially affecting about one-fourth of MDD cases.  CBMJ 2026 January: vol. 15 no. 01 P:162-167